Quantification of O-(2-[(18)F]fluoroethyl)-L-tyrosine kinetics in glioma - Koopman, Thomas (EJNMMI Res, 2018)
BACKGROUND: This study identified the optimal tracer kinetic model for quantification of dynamic O-(2-[(18)F]fluoroethyl)-L-tyrosine ([(18)F]FET) positron emission tomography (PET) studies in seven patients with diffuse glioma (four glioblastoma, three lower grade glioma). The performance of more simplified approaches was evaluated by comparison with the optimal compartment model. Additionally, the relationship with cerebral blood flow—determined by [(15)O]H(2)O PET—was investigated. RESULTS: The optimal tracer kinetic model was the reversible two-tissue compartment model. Agreement analysis of binding potential estimates derived from reference tissue input models with the distribution volume ratio (DVR)-1 derived from the plasma input model showed no significant average difference and limits of agreement of − 0.39 and 0.37. Given the range of DVR-1 (− 0.25 to 1.5), these limits are wide. For the simplified methods, the 60–90 min tumour-to-blood ratio to parent plasma concentration yielded the highest correlation with volume of distribution V(T) as calculated by the plasma input model (r = 0.97). The 60–90 min standardized uptake value (SUV) showed better correlation with V(T) (r = 0.77) than SUV based on earlier intervals. The 60–90 min SUV ratio to contralateral healthy brain tissue showed moderate agreement with DVR with no significant average difference and limits of agreement of − 0.24 and 0.30. A significant but low correlation was found between V(T) and CBF in the tumour regions (r = 0.61, p = 0.007). CONCLUSION: Uptake of [(18)F]FET was best modelled by a reversible two-tissue compartment model. Reference tissue input models yielded estimates of binding potential which did not correspond well with plasma input-derived DVR-1. In comparison, SUV ratio to contralateral healthy brain tissue showed slightly better performance, if measured at the 60–90 min interval. SUV showed only moderate correlation with V(T). V(T) shows correlation with CBF in tumour. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13550-018-0418-0) contains supplementary material, which is available to authorized users.